Assessment of the quality attributes and oxidative stability of fish balls with the addition of fig powder during frozen storage - Md. Sakib Hasan; Md. Nowshad Mahmud Choyon; Md. Numan Islam; Md. Golam Rabby; Ananya Raiyan; Md. Mohaiminul Islam; Nishat Tabassum Prokrite; Md. Abid Hassan; Nishat Chadni Liza; Suvasish Das Shuvo; Rashida Parvin; Md. Ashrafuzzaman Zahid (PLoS ONE, 2025)
This study evaluated the oxidative stability and physicochemical attributes of fish balls made from Pangasius pangasius (Pangus) by the addition of natural antioxidant Ficus carica (Fig fruit) and other synthetic antioxidants, Butylated hydroxytoluene (BHT) and Ascorbic Acid (AA), and the fish balls were stored under freezing conditions for two months. Four different types of fish balls were made with or without antioxidants: 1) T0 (without antioxidants); 2) T1 (0.02% BHT); 3) T2 (0.05% AA); 4) T3 (1% fig powder). Incorporating antioxidants significantly retained ( p < 0.05) lower TBARS, pH, and yellowness while holding higher DPPH and redness values throughout storage. The addition of fig powder (FP) significantly ( p < 0.05) reduced oxidation, free radical scavenging activity, and pH values. The fig’s antioxidant potential was non-significantly ( p > 0.05) different from BHT and AA. Moreover, the fig retained a significantly higher moisture content ( p < 0.05), essential for maintaining fish ball quality. Furthermore, the cooking loss increased non-significantly ( p > 0.05) among treated samples due to lower moisture and fat loss. Sensory assessment regarding color values of all treated and non-treated samples, FP showed a significantly ( p < 0.05) higher redness value and a significantly ( p < 0.05) lower yellowness when compared to control samples throughout the storage period. Therefore, adding FP as a natural antioxidant could reduce oxidation and maintain the others physicochemical characteristics of fish balls under freezing conditions.